Analysis of Achievement, Motivation and Self-Efficacy among Undergraduate Nursing Students : Analysis of Achievement, Motivation and Self-Efficacy - Kausar, Tanveer; Fatima, Fozia; Naureen, Asma; Yasmeen, Shahida; Noreen, Safia; Tariq, Rubab; Siddiqi, Fuad Ahmad (Pakistan Journal of Health Sciences, 2024)
Strong self-efficacy enhances motivation and performance, while strong achievement motivation boosts self-efficacy. Objective: To determine achievement motivation and self-efficacy levels among undergraduate nursing students. Methods: A cross-sectional study was conducted from September 2023 to July 2024 at three nursing institutes. A total of 222 undergraduate nursing students participated using convenience sampling. Data were collected through a self-efficacy questionnaire developed by Ralf Schwarzer. Achievement motivation was measured using McInerney’s tool. Data analysis was performed using SPSS version 21.0. Results: Most participants were females, with 90.1% aged 20–25. The study was conducted at the College of Nursing Rawalpindi and PIMS Islamabad. Findings indicated that participants with confidence in their skills, improvement in work, and good academic performance had the highest motivation levels. External factors, such as praise or awards, were less influential. The average achievement-oriented behavior score was 4.12. Self-efficacy data revealed varied confidence levels, with most participants believing they could learn challenging content, overcome obstacles, influence personal growth, maintain relationships, and solve problems innovatively. The average self-efficacy score was also 4.12, indicating high confidence. Conclusions: The research highlights that highly motivated individuals achieve better outcomes, demonstrate faith in their skills, and perform well academically. Motivation is primarily driven by intrinsic factors like self-efficacy and personal growth, rather than external recognition. Enhancing self-efficacy and intrinsic motivation is crucial to improving overall performance, emphasizing persistence, diligence, and innovation as key drivers of success.